2015
DOI: 10.1007/s10554-015-0795-7
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of sub-millisievert coronary CT angiography with low tube voltage, prospective ECG gating, and a knowledge-based iterative model reconstruction algorithm

Abstract: We evaluated the feasibility of sub-millisievert (mSv) coronary CT angiography (CCTA) using low tube voltage, prospective ECG gating, and a knowledge-based iterative model reconstruction algorithm. Twenty-four non-obese healthy subjects (M:F 13:11; mean age 50.2 ± 7.8 years) were enrolled. Three sets of CT images were reconstructed using three different reconstruction methods: filtered back projection (FBP), iterative reconstruction (IR), and knowledge-based iterative model reconstruction (IMR). The scanning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
2
15
1
Order By: Relevance
“…Third, although retrospectively ECG-triggered MDCTA more clearly depicts ventricular morphology than helical CT scanning mode, retrospective ECG-gating is currently not recommended as a routine MDCTA protocol because of its higher radiation dose compared with helical scanning mode. Recent studies showed that the use of prospective ECG-gating significantly reduces the radiation exposure to patients undergoing MDCTA and yields diagnostic image quality in the assessment of coronary arteries [ 42 45 ], coronary artery bypasses [ 46 ], and congenital heart disease [ 47 ] with lower radiation dose. Future studies are warranted that evaluate the diagnostic accuracy of low-dose prospectively ECG-triggered MDCTA in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although retrospectively ECG-triggered MDCTA more clearly depicts ventricular morphology than helical CT scanning mode, retrospective ECG-gating is currently not recommended as a routine MDCTA protocol because of its higher radiation dose compared with helical scanning mode. Recent studies showed that the use of prospective ECG-gating significantly reduces the radiation exposure to patients undergoing MDCTA and yields diagnostic image quality in the assessment of coronary arteries [ 42 45 ], coronary artery bypasses [ 46 ], and congenital heart disease [ 47 ] with lower radiation dose. Future studies are warranted that evaluate the diagnostic accuracy of low-dose prospectively ECG-triggered MDCTA in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] have also reported accurate noninvasive diagnosis of coronary artery disease with the use of a model-based IR-reconstructed CCTA. In our previous study, we reported the feasibility of using CCTA with 80 kVp, 200 mAs, prospective ECG gating, and an IMR algorithm to produce images of markedly higher quality (3.6 ± 0.6), compared with the use of IR and FBP (3.1 ± 0.7 for IR; 2.3 ± 0.6 for FBP, p < 0.01) [ 26 ]. However, to our knowledge, no study has compared the effectiveness of a reduced tube voltage (80 kVp) combined with IMR to the widely used 100 kVp CCTA protocol combined with IR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, state-of-the-art CT scanners offer special acquisition modes as high volume axial modes or high-pitch spiral dual source protocols. In combination with advanced reconstruction algorithms radiation doses below 1.0 mSv for CCTA can be reached [37,38].…”
Section: Cct Image Acquisitionmentioning
confidence: 99%